2018
DOI: 10.1016/j.joca.2018.02.596
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cell therapy for osteoarthritis: how apoptotic cells modulate inflammation

Abstract: Purpose: Mesenchymal stem cells (MSCs) enhance regeneration when locally delivered in pre-clinical models of osteoarthritis (OA). Their mechanism of action, however, is still poorly understood. Preliminary data show low engraftment of GFP-expressing syngeneic MSCs in mouse knee joints, consistent with published data using molecular techniques. We hypothesise that implanted cells undergo apoptosis or cell death. There is growing evidence that apoptotic MSCs exert an antiinflammatory effect, by release of immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…One can consider inhibiting NO to prolong MSC survival, noting that it also will restrict the immunosuppression capacity of MSCs on the lymphocytes. Interestingly, Mancuso et al's study of knee osteoarthritis using an in vitro model revealed that apoptotic MSCs were more immunosuppressive than healthy MSCs [63]. Moreover, Chang et al SDF-1: stromal cell-derived factor 1; SCF: stem cell factor; IL-6: interleukin-6; VEGF: vascular endothelial growth factor; bFGF: basic fibroblast growth factor; PDGF: platelet-derived growth factor; ROS: reactive oxygen species; RNS: reactive nitrogen species; EGF: epidermal growth factor; HGF: hepatocyte growth factor; NGF: nerve growth factor; TGF-β: transforming growth factor-beta; LIF: leukemia inhibitory factor; NO: nitric oxide; CCL: C-C motif chemokine ligand (created with BioRender.com).…”
Section: Necrobiologymentioning
confidence: 99%
“…One can consider inhibiting NO to prolong MSC survival, noting that it also will restrict the immunosuppression capacity of MSCs on the lymphocytes. Interestingly, Mancuso et al's study of knee osteoarthritis using an in vitro model revealed that apoptotic MSCs were more immunosuppressive than healthy MSCs [63]. Moreover, Chang et al SDF-1: stromal cell-derived factor 1; SCF: stem cell factor; IL-6: interleukin-6; VEGF: vascular endothelial growth factor; bFGF: basic fibroblast growth factor; PDGF: platelet-derived growth factor; ROS: reactive oxygen species; RNS: reactive nitrogen species; EGF: epidermal growth factor; HGF: hepatocyte growth factor; NGF: nerve growth factor; TGF-β: transforming growth factor-beta; LIF: leukemia inhibitory factor; NO: nitric oxide; CCL: C-C motif chemokine ligand (created with BioRender.com).…”
Section: Necrobiologymentioning
confidence: 99%
“…BMSCs secrete various bioactive factors and stromal molecules to regulate the damaged tissue environment and direct subsequent regenerative processes, including cell migration, proliferation, and differentiation . Research has shown that MSCs transplantation can boost the microenvironment of the regenerated injured site, accelerating tissue repair and regeneration. Ando et al generated a MSC-based tissue-engineered construct (TEC) to facilitate in vivo repair in a porcine chondral defect model; repaired tissue after TEC implantation exhibited levels of chondrogenic differentiation and integration similar to those in immature porcine experiments here. Zhang et al studied that BMSCs enhanced articular chondrocyte proliferation and migration, anabolic gene expression in the extracellular matrix, especially chondrocytes, and articular cartilage generation in vivo .…”
Section: Introductionmentioning
confidence: 91%